Pengukuran Tingkat Kesiapan E-learning Guru di Kota Jayapura di Masa Pandemik Covid-19 - Remuz Maurenz Bertho Kmurawak; Samuel Alexander Mandowen (Techno.Com, 2021)
E-learning is one of the revolutions in the education system that encourages the acceleration of quality learning. The Covid-19 pandemic has become a catalyst for accelerating the implementation of e-learning in Jayapura, Papua. Teachers are required to be able to adapt to this rapid change. Thus, E-learning becomes essential amid the pandemic, yet the ICT indicators reveal many barriers to implementing it. This study aims to assess the level of readiness of the teachers in implementing the e-learning system. Data was collected by distributing questionnaires to the teachers from elementary to high school in Jayapura City. Technology infrastructures, human resources, and e-learning content were the main variables to measure. This study indicated that based on teachers' perceptions, more than 70 percent were using google classroom as an e-learning platform. The level of readiness was level 3 (ready with minor improvements). Infrastructures, internet access, and e-learning content availability are the indicators that needed extra attention for improvement